LEGAL CONSEQUENCES OF NAME-CHANGING PERSON IN OFFICIAL STATE DOCUMENTS: A CIVIL LAW REVIEW - Wirianistiati, Ardianita; Sadjijono, Prof. Dr. Sadjijono (YURIS: Journal of Court and Justice, 2022)
Changing the name is basically changing the person’s identity on birth certificate. For its validity, name changing must meet the procedures contained in Law Number 23 of 2006. This research aims to find out the procedure for changing names in official state documents and the consequences of changing one's name in official state documents which are not procedural in terms of civil law. In conducting this research, normative legal research will be used by reviewing the existing laws and regulations. Name changing will have legal consequences for the new name and the legal status of official document will affect the changed name, but the rights and obligations will remain same. This happened because they were the same person, but their rights and obligations changed to different name that was obtained from local district court decision. The name changing will cause problems in population administration when it is not meet the procedure. Then, it is essential to follow the existing procedural in changing the name.